Recurrence Rate of Pterygium Between Amniotic Membrane versus Stem Cell Graft following Pterygium Excision (Medical Forum Monthly, 2024)
Objective: To find out and compare the recurrence rate of pterygium using amniotic membrane versus stem cell graft techniques following the excision of pterygium.Study Design: A single open label, randomized control trial.Place and Duration of the Study: This study was conducted at the Department of Ophthalmology, Bahawal Victoria Hospital, Bahawalpur, from July 2016 to June 2017.Materials and Methods: We enrolled a total of 80 patients of both gender, aged more than 18 years, having grade 2-3 of pterygium causing discomfort, impairment of vision or disfigurement, undergoing pterygium excision. Group A contained 40 patients and pterygium excision was done using amniotic membrane grafting (AMG) whereas Group B had 40 patients where stem cell graft (SCG) was performed. Mean and standard deviations were calculated for continuous variables while frequency and percentages were estimated for quantitative variables. Chi square test was applied and p value < 0.05 was considered as significant.Results: There were 44 (55.0%) male and 36 (45.0%) female. Mean age was recorded as 40.73 years with a standard deviation of 8.6 years.In terms of grafting edema, 1 (2.5%) patient was observed in Group A while there were 5 (12.5%) patients having grafting edema in Group B (p value = 0.090). Hemorrhage was reported in 5 (12.5%) patients of Group A as compared to 2 (5.0%) in Group B (p value = 0.235). Pterygium recurrence was noted in 6 (15.0%) patients of Group A in comparison to 2 (5.0%) in Group B (p value = 0.136).Conclusion: Although in terms of complications and recurrence, no major statistical difference was found in between the two studied group, SCG was associated with less recurrence rate following pterygium excision.